Encontros formativos de um coletivo docente em uma escola pública de educação infantil - Haetinger, Célia Beatris Garcia (2024)
The research is linked to the Professional Master's Degree at the Federal University of Santa Maria (UFSM) in Research Line 2 – Pedagogical Management and Educational Contexts. This work was developed in a public early childhood education school in the interior of Rio Grande do Sul, in the city of Cachoeira do Sul, EMEI APCRIM. The study was guided by the following problem: What training paths do EMEI APCRIM teachers take to build pedagogical work committed to childhood? The general objective was based on: Researching which training paths EMEI APCRIM teachers follow to build pedagogical work committed to childhood. And as specific objectives: - Enable connections between the path taken by the researcher and the work context at EMEI APCRIM. - Build a collaborative training path with the teaching group. - Describe which educational policies for Early Childhood Education have been developed within the scope of the Cachoeira do Sul Municipal Education System, in line with national legislation. - Draw lines of encounters and distances between the teacher training processes proposed by the municipality and the EMEI APCRIM Continuing Training Project. - Dialogue with the data collected, in order to reflect on how teacher training processes have been constructed in the researched school. - Share/present, through the creation of an educational product materialized in a Digital Portfolio, the trajectories and processes of training in the context of EMEI APCRIM teachers. The methodological path will be carried out based on research with a qualitative approach, applied and involved in the context of this researcher's work and through craftsmanship (MILLS, 2009) and complexity (MORIN, 2000). The theoretical framework of this study is based on Freire (2018), Oliveira-Formosinho (2018), Minayo (2019), Morin (2000), Mills (2009), among others. The process of this work will be described through training meetings that take place monthly with the group of professionals who work at the school, teachers. As a product, a digital portfolio that has been produced will be presented at the end of the research and will be delivered to the Municipal Department of Education as a proposal for future reflection.